2018
DOI: 10.1111/cxo.12557
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy of topical azithromycin 1.5 per cent ophthalmic solution for the treatment of meibomian gland dysfunction

Abstract: Background:The aim was to evaluate the clinical efficacy of topical azithromycin 1.5 per cent ophthalmic solution in treatment of the clinical signs and symptoms associated with meibomian gland dysfunction (MGD). Methods: In this retrospective study, 35 patients with MGD were treated with topical azithromycin 1.5 per cent ophthalmic solution for 30 days. Topical azithromycin 1.5 per cent ophthalmic solution was prescribed twice daily for two days and then once daily for a total of 30 days. Daily lid hygiene wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…38 Azithromycin could help improve clinical signs and parameters, such as tear film break-up time, Schirmer test, and meibomian gland plugging, of patients with MGD. [39][40][41] In this study, we found conjunctival sac bacterial imbalances in patients with MGD. Overgrowth of Staphylococcus and Sphingomonas provided microbiological evidence for investigating the mechanisms of the efficacy of antibiotics in MGD.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…38 Azithromycin could help improve clinical signs and parameters, such as tear film break-up time, Schirmer test, and meibomian gland plugging, of patients with MGD. [39][40][41] In this study, we found conjunctival sac bacterial imbalances in patients with MGD. Overgrowth of Staphylococcus and Sphingomonas provided microbiological evidence for investigating the mechanisms of the efficacy of antibiotics in MGD.…”
Section: Discussionsupporting
confidence: 49%
“…In our study, all patients with MGD had different degrees of bacterial imbalance in the conjunctival sac, and dysbacteriosis occurred in severe cases. Because antibiotic treatment can alleviate clinical symptoms of patients with severe MGD, 18,[37][38][39][40] it can be speculated that dysbacteriosis linked closely with the disease process, despite the unclear mechanisms. However, the conditions of patients with MGD are usually complicated, and some cases overlap with other diseases, such as blepharitis and dry eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…People who suffer from acne rosacea or seborrheic dermatitis or psoriasis are more prone to have MGD than the general population [ 3 ]. Complicated pathogenesis of the disease combined with the cutaneous conditions makes it hard to manage, while the current means of therapy are limited [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve better therapeutic effects, combined means are always employed to treat the disease because both inflammatory and bacterial elements are involved in the development of MGD [ 5 ]. To date, eyelid hygiene, lid massage, warm compresses, artificial tears, and topical antibiotics are routine ways to treat the disease [ 4 ]. In addition, topical steroids and/or immunosuppressive agents (e.g., cyclosporine A, Cs A) have been used in some cases and gained satisfactory outcomes, but the complications from steroids and high cost of Cs A cannot be ignored for long-term use [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation